2020
DOI: 10.1155/2020/6415432
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Response of HIV-Infected Children to Different Regimens of Antiretroviral Therapy: A Retrospective Observational Study

Abstract: Background. Both abacavir- (ABC-) based and zidovudine- (AZT-) based regimens are widely utilized for managing HIV infection in children. Unfortunately, there is a lack of data regarding their immunological response and associated risk factors in Ethiopia. Methods. A retrospective hospital-based cohort study was conducted on HIV-infected children in Jimma Medical Center (JMC). A total of 179 records were reviewed by including data from November 2015 to April 2017. Data were collected on sociodemographic, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…As a consequence, mortality in HIV patients has decreased significantly [2][3][4]. However, drug-induced side effects associated with longterm antiretroviral therapy are becoming a growing concern [2,3,5]. HIV therapy involves highly active antiretroviral therapy (HAART), meaning that patients are treated with drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, mortality in HIV patients has decreased significantly [2][3][4]. However, drug-induced side effects associated with longterm antiretroviral therapy are becoming a growing concern [2,3,5]. HIV therapy involves highly active antiretroviral therapy (HAART), meaning that patients are treated with drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…12 (50%) were prospective cohort studies, 15,[22][23][24][25][26][27][28][29][30][31][32] including one cohort nested in an RCT. 22 Seven (29%) were retrospective cohort studies 14,[33][34][35][36][37][38] and two (8%) were crosssectional surveys. 19,39 These studies were conducted in various settings; nine (38%) in southern Africa (Zambia, South Africa, and Zimbabwe), six (25%) in eastern Africa (Ethiopia, Uganda, and Malawi), two (8%) in western Africa (Ghana and Nigeria), three (13%) in south Asia (India), three (13%) in Europe, and three (13%) in North America.…”
Section: Resultsmentioning
confidence: 99%
“…One study showed higher CD4 count gain at 6 months for zidovudinebased regimens compared with abacavirbased regimens. 37 Most outcomes were reported heterogeneously between studies, and except for two randomised trials, studies were considered of moderate to high risk of bias. Therefore, data inter pretation needs to be made cautiously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many children are inclined to exhibit poor immunologic response due to the variations arising from the response to therapy that may increase their risk of morbidity and mortality despite the widespread use of cART 23,24 . In prior studies, a multitude of sociodemographic and clinical parameters have been found to in uence IR in HIVinfected pediatric patients following cART initiation: Baseline CD4 + lymphocyte count, cART group, WHO clinical stages, initial nutritional status, tuberculosis and the presence of anemia have all been found to in uence CD4 + count reconstitution 23,24 . Nonetheless, with the existing data and the lines of evidence, the depth of knowledge in the Sub-Saharan context remains sparse.…”
Section: Introductionmentioning
confidence: 99%